Diseño de prototipo de una máquina trituradora de plásticos PET” - Saquinga Moposita, Bryan Stalin (2024)
In order to address the utilization limited issue of PET material in relation to volume/weight, which has led to a considerable increase in the recycling process, it has been decided to manufacture a shredder machine to reduce plastic volume by 85% and facilitate its reuse in other processes. For this purpose, an exhaustive literature review was conducted based on design and component selection. However, before proceeding with the design, key parameters were identified, such as critical bottle thickness, selection of material type for blade fabrication, dimension of the optimal grip between blade/bottle, and determination of crushing capacity as a time function. The optimization of this design process was carried out using CAD-CAE tools to ensure the design and stability of the shredder machine, periodically analyzing the components behavior such as blades, crushing shafts, and its structure base. Taking into consideration the tensile strength of plastic (90 MPa), blades manufacturing in ASTM A36 steel with a thickness of 8mm and a diameter of 100mm has been complemented. According to finite analysis, this blade has a shear stress of 126.6 MPa, sufficient for plastic crushing, with a safety factor of 2. Once the machine was completed, various performance tests were conducted, resulting in the following output variables: a crushing time of 15.20 seconds per 200 grams of shredded material, which aligns with maximum hopper dimensioning, a minimum particle size of 8x12 mm and a maximum of 8x66 mm, and an energy consumption of 0.00942 kW per crushing cycle. Therefore, this machine was manufactured to meet an improvement in less volume of PET plastic.